Pengembangan Instrumen Tes Diagnostik Five-Tier untuk Mengidentifikasi Miskonsepsi Siswa Kelas XI pada Materi Laju Reaksi - Khairunnisa Khairunnisa; Ajat Sudrajat (PendIPA Journal of Science Education, 2023)
This study aimed to report the results of the validity and reliability test of the five-tier diagnostic test instrument on the reaction rate material and identify the level of misconceptions experienced by students of class XI IPA MAN 2 Model Medan on the concept of the material. This research was conducted in November-March 2022/2023 academic year. This research was a descriptive research using the ADDIE development model. Data collection in this study used tests, interviews and questionnaires. The research stage begins with data collection and literature study, initial needs analysis, product design stage, development of five-tier diagnostic test instruments and validation by experts, test validity and reliability of tests on small-scale trials and identification of student misconceptions on broad-scale trials. The assessment results from expert validators show the criteria of the instrument developed are valid. The results of the item validity analysis obtained 23 valid items and 7 invalid items. Based on the reliability test results, it is known that the five-tier diagnostic test instrument has high reliability with a reliability coefficient of 0.80. The results of the broad-scale trial showed that the level of misconceptions of students in the XI Science class of MAN 2 Medan Model on the reaction rate material was 33% which was classified in the moderate category. The largest percentage of misconceptions is on the concept of reaction order and reaction rate equation of 46.75%. The lowest percentage of misconceptions experienced by students is in understanding the concept of factors that affect the reaction rate of 20.27%.